THE ROLE OF THE POLITICAL KESBANG AGENCY AND FKUB IN MAINTAINING THE HARMONY OF THE UMMAH INTRODUCTION - Baso Sulaiman (RADJA PUBLIKA, 2026)
This study aims to analyze the role of the National Unity and Political Agency ( Kesbangpol ) and the Forum for Religious Harmony (FKUB) in maintaining interreligious harmony in Palopo City. Indonesia, as a multicultural country, demonstrates a relatively high level of religious harmony; however, challenges remain, particularly in the aspect of tolerance. This research employs a qualitative approach, with data collected through interviews, observations, and documentation studies. The findings indicate that Kesbangpol , together with FKUB, plays strategic roles as a facilitator, educator, and promoter by involving various actors such as community organizations, religious leaders, traditional leaders, and academics. Program implementation is carried out through interfaith dialogue, joint social activities, and community empowerment based on religious groups. In addition, the institutional strategies applied include strengthening community relations, community empowerment, and community services. The findings in Palopo City reveal a high level of tolerance, equality, and cooperation among religious communities, as reflected in the harmonious social life of the society. Therefore, the roles of Kesbangpol and FKUB are proven to be effective in maintaining stability and interreligious harmony through collaborative and participatory approaches